Why is the Burden Reduction Work at the Grassroots Level "Often Reduced with Often Negative"? Take X Community in Yibin City as an Example - Yang, Lichen (International Journal of Social Sciences and Public Administration, 2025)
Based on the explanatory framework of structural functionalism, the case analysis of community grassroots burden reduction shows that the problem of "constant reduction and constant negative" of grassroots work is rooted in environmental adaptation, goal achievement, integration and coordination and model maintenance, the external environment increases the work pressure through the adjustment of organizational goals, and the work objectives are transmitted to the grassroots organizations layer by layer, and the functional integration and coordination within the organization increases the burden on the grassroots to a certain extent, and the feedback mode of the assessment of the superior department and external supervision increases the workload of the grassroots level, thus forming a model cycle of "constant reduction and constant negative". Based on this, grassroots organizations should strengthen the level of environmental capacity adaptation, straighten out the relationship between lines and powers, optimize organizational integration and coordination functions, and build an effective model maintenance mechanism, so as to reduce the burden on the grassroots level.